PUBLIC ASSISTANT MANAGEMENT FOR UPOSATHASILA OBSERVING OF WATBANGSRAKAO BANGSRAKAO SUBDISTRICT, LAEMSING DISTRICT, CHANTHABURI PROVINCE - พระปลัดสาธิต สุจิณฺโณ; พระปลัดระพินพุทฺธิสาโร; ธิติวุฒิ หมั่นมี (Journal of MCU Social Science Review, 2020)
The objectives of this research were: 1) to study the construction management for eight precepts keeping of Wat Bangsrakao, Bangsrakao district, Laemsing district, Chanthaburi province, 2) to study the problems , obstacles and suggestions for development to the construction management for eight precepts keeping of Wat Bangsrakao, Bangsrakao district, Laemsing district, Chanthaburi province. This research is the mixed research method. For the quantitative research is the survey research from the questionnaire and quanlitative research is the in depth interview from key informants. For the support the quantitative data , the population for this research is the eight precepts keepers whom come to keep the precepts at Wat Bangsrakao, Bangsrakao district, Laemsing district, Chanthaburi province by the simple sampling group from Krejcie and Morgan formula. The 250 people as the sampling population.The data analysis is also used by the ready programme for research of social sciences. The researcher had the data analysis through frequency, percentage, mean, standard deviation(S.D) one-way analysis of variance (One-way ANOVA) for testing the difference between the averages from three or more groups with LSD (Least Significant Different) at significantly statistics at 0.05. The research findings were as follows: The majority of correspondents was the female for 182 persons or 72.8 percent, having the marital status for 144 persons or 57.6 percent , having the age more than 50 years old for 224 persond or 89.6 percent , having the education from primary school for 220 persons or 88 percent , having the career as farmers as 133 persons or 53.2 percent and having the income per month 4000 – 7000 Baht for 157 persons or 62.8 percent. The construction management for eight precepts keeping of Wat Bangsrakao, Bangsrakao district, Laemsing district, Chanthaburi province 1. The environment : The problem and obstacle like the toilet is old and the elderly are not convenient to use it, lack of budget to develop the readiness , suitability, sufficiency for using. Suggestions : should improve the toilet for the elderly to use easily, should allocate the budget from the public sector and private sector. 2. The form of ritual ceremony : The problem and obstacle are the small numbers of ritual ceremony masters , the triual ceremony masters lack of knowledge according to traditional ceremony that makes the traditional ceremony fades away, the small numbers of precept keepers, lack of Vappassana monks or meditation masters to teach the meditation and introducing the way to chant. Suggestions : should cultivate the youths to know the eight precepts keeping and to increase the learning process of traditional ceremony , cooperate with other agencies or related organizations for campaigning the people to see the importance of the eight precepts keeping for motivation creation. 3. The demand : The problem and obstacle lack of budget for reconstruction, development and create the environment of chanting hall properly and sufficiently. Suggestion : should allocate the budget that support by the public sector and private sector.